APPLICATION OF A FUZZY CONTROLLER IN THE PROCESS OF AUTOMATED POLYETHYLENE FILM THICKNESS CONTROL - Jardzioch, Andrzej; Marczak, Wioletta (Applied Computer Science, 2021)
The present article aims to describe the design of a fuzzy controller used for automated control of the thickness of the extruded polyethylene film effected by the adjustment of the actuator in the cooling ring. In order to determine whether the designed controller operates properly, a model extruder was created and a simulation study was carried out. The Simulink programming environment integrated with Matlab was used for the development of the fuzzy controller and the simulation. The conducted simulation study demonstrated that the implementation of the designed controller would enable the adjustment of thickness on the perimeter of the film tube and quick reaction to possible departure in the assumed film thickness in mass production.